Pulmonary consequences of experimentally induced stroke: differences between global and focal cerebral ischemia - Somogyi, Petra; Tóth, Ibolya; Ballók, Bence; Hammad, Zaid; Hussein, Ramez A.; Kun-Szabó, Fruzsina; Tolnai, József; Danis, Judit; Kecskés, Szilvia; Fodor, Gergely H.; Farkas, Eszter; Peták, Ferenc (Frontiers in Physiology, 2024)
IntroductionCerebral ischemia leads to multiple organ dysfunctions, with the lungs among the most severely affected. Although adverse pulmonary consequences contribute significantly to reduced life expectancy after stroke, the impact of global or focal cerebral ischemia on respiratory mechanical parameters remains poorly understood.MethodsRats were randomly assigned to undergo surgery to induce permanent global cerebral ischemia (2VO) or focal cerebral ischemia (MCAO), or to receive a sham operation (SHAM). Three days later, end-expiratory lung volume, airway and respiratory tissue mechanics were measured at positive end-expiratory pressure (PEEP) levels of 0, 3 and 6 cmH2O. Bronchial responsiveness to methacholine, lung cytokine levels, wet-to-dry ratio, blood gas parameters and cerebral stroke markers were also evaluated.ResultsGlobal and focal cerebral ischemia had no significant effect on end-expiratory lung volume, bronchial responsiveness, and arterial blood gas levels. No change in respiratory mechanics and inflammatory response was evident after 2VO. Conversely, MCAO decreased airway resistance at PEEP 0, deteriorated respiratory tissue damping and elastance at all PEEP levels, and elevated Hct and Hgb. MCAO also caused lung edema and augmented IL-1β and TNF-α in the lung tissue without affecting IL-6 and IL-8 levels.DiscussionOur findings suggest that global cerebral ischemia has no major pulmonary consequences. However, deteriorations in the respiratory tissue mechanics develop after permanent focal ischemia due to pulmonary edema formation, hemoconcentration and cytokine production. This respiratory mechanical defect can compromise lung distension at all PEEP levels, which warrants consideration in optimizing mechanical ventilation.